Transformasi Komunikasi Keluarga Muslim di Era Digital: Pemanfaatan Smartphone pada Masyarakat Pedesaan, Kabupaten Tabalong, Kalimantan Selatan - Rizki Apriliyanti; Ahmad Yazid Imani; Nasrudin Nasrudin (Mahad Al Jamiah UIN Syarif Hidayatullah Jakarta, 2026)
Digital transformation has reshaped patterns of family communication, including among rural communities that have begun adopting smartphone technology. Smartphones no longer function merely as communication devices but have become part of a broader social practice that influences how families interact, share information, and build relationships among their members. This study aims to analyze the transformation of family communication through smartphone use in a rural community, focusing on changes in parent–child interaction patterns, the process of communication adaptation, and the distribution of digital knowledge within the family. Employing a qualitative approach with a case study method, the research was conducted in Harus Village, Tabalong Regency, South Kalimantan. Data were collected through in-depth interviews, observation, and documentation involving 13 parents as informants, and analyzed through data condensation, data display, and conclusion drawing/verification. The findings reveal that smartphones have undergone a process of domestication, becoming embedded in everyday family communication. Smartphone use expands interactional space through digital applications, supports children's educational activities, and facilitates family coordination. Families are nonetheless required to continually adapt their technology management practices to preserve the quality of interaction. The study demonstrates that smartphones do not replace face-to-face communication but instead give rise to a hybrid communication pattern that combines direct interaction with digital communication within rural families.